Development of Contemporary Islamic Law - Randi Hermawan; Rabiul Awaluddin (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
A concise and concise summary is required (maximum 250 words). The summary should briefly indicate the purpose of the study, the material method, its main results and its major results. The summary is often presented separately from the article, so you need to be able to stand alone. For this reason references should not be used. Times New Roman; 10 pt. Shortly after the summary, provide up to 4-6 keywords avoiding general and plural terms and multiple concepts (eg